2019
DOI: 10.1038/s41467-019-12143-3
|View full text |Cite
|
Sign up to set email alerts
|

USP7 inhibits Wnt/β-catenin signaling through promoting stabilization of Axin

Abstract: Axin is a key scaffolding protein responsible for the formation of the β-catenin destruction complex. Stability of Axin protein is regulated by the ubiquitin-proteasome system, and modulation of cellular concentration of Axin protein has a profound effect on Wnt/β-catenin signaling. Although E3s promoting Axin ubiquitination have been identified, the deubiquitinase responsible for Axin deubiquitination and stabilization remains unknown. Here, we identify USP7 as a potent negative regulator of Wnt/β-catenin sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(88 citation statements)
references
References 60 publications
3
78
6
1
Order By: Relevance
“…We also observed an increase in p‐β‐catenin (Ser33/Ser37/Thr41) and a decrease in active β‐catenin and p‐GSK3 (phosphorylated at Ser9) levels is a response to combined treatment, especially after 48 hr, as measured by western blot analysis and densitometry (Figure c). Active β‐catenin represents the stabilized form of β‐catenin, that is not phosphorylated by GSK3β (Ji et al, ). Taken together, these results indicated that the combination of the two drugs dampened Wnt/β‐catenin signaling pathway, most likely through the activation of GSK3β and proteasomal degradation of β‐catenin.…”
Section: Resultsmentioning
confidence: 99%
“…We also observed an increase in p‐β‐catenin (Ser33/Ser37/Thr41) and a decrease in active β‐catenin and p‐GSK3 (phosphorylated at Ser9) levels is a response to combined treatment, especially after 48 hr, as measured by western blot analysis and densitometry (Figure c). Active β‐catenin represents the stabilized form of β‐catenin, that is not phosphorylated by GSK3β (Ji et al, ). Taken together, these results indicated that the combination of the two drugs dampened Wnt/β‐catenin signaling pathway, most likely through the activation of GSK3β and proteasomal degradation of β‐catenin.…”
Section: Resultsmentioning
confidence: 99%
“…Scaffolding protein AXIN is the rate-limiting component of the β-catenin destruction complex, which are constantly surveyed and regulated by tankyrases [56][57][58]. Tankyrases belong to the Poly (ADP-ribose) polymerases (PARPs) family, regulating the stability of AXIN1 and AXIN2 through directing AXIN ubiquitylation by RNF146 and proteasomal degradation [59,60].…”
Section: Agents Targeting the β-Catenin-destruction Complex Tankyrasementioning
confidence: 99%
“…[313][314][315] In addition, the deubiquitinating enzymes USP34/USP7, CYLD/USP9X and USP4 can bind to Axin, Dvl and β-catenin, respectively, thereby promoting the nuclear localization of β-catenin and the Wnt signaling pathway by inhibiting their ubiquitination. [316][317][318][319][320] Ubiquitination in the Hippo-YAP signaling pathway In mammals, the Hippo signaling pathway can also maintain CSC stemness, regulate cell growth, control the size of organs and take part in tumorigenesis. 321,322 Ubiquitination also plays an important role in regulating the Hippo signaling pathway, with a variety of E3 ligases being identified.…”
Section: Nanog Ubiquitinationmentioning
confidence: 99%